What is the effectiveness of radiofrequency ablation in the management of patients with spinal metastases? A systematic review and meta-analysis - Navanith Murali (BMC, 2021)
Abstract Purpose Spinal metastases are indicative of progressive cancer which can lead to vertebral body fractures and spinal cord compression. Radiofrequency ablation (RFA) treatment is infrequently used in patients with refractory pain. The aim of this systematic review is to determine the clinical efficacy of RFA, with the scope of using it as front-line management of spinal metastases. Methods Electronic databases were searched (to July 2020) for studies evaluating RFA treatment for spinal metastases in adults. Measured outcomes were pain (primary), disability, health-related quality of life (HRQOL), complications, tumour control and mortality. Study inclusion, data extraction and risk of bias using the ROBIN-I tool were assessed. Meta-analysis was conducted for pooled results with homogeneity, and narrative synthesis was conducted otherwise. Results 15 studies were included. RFA reduces pain scores at 3–5 weeks [standardised mean difference (SMD 2.24, 95% confidence intervals (CI) 1.55–2.93], 3–4 months (SMD 3.00, 95% CI 1.11–4.90) and 5–6 months (SMD 3.54, 95% CI 1.96–5.11). RFA is effective in reducing disability/improving HRQOL in the short-term but longer-term efficacy remains unclear. 13.2% cases reported local tumour control failure (2.5 months–5 year follow-up) whereas mortality was 23.6% (follow-up of up to 1 year). Conclusion Low quality evidence has proven RFA to be safe and effective in reducing pain and disability, especially in the short-term. RFA may be routinely implemented in all cases involving refractory pain or radiotherapy-resistant tumours but controlled trials are required to compare the efficacy of RFA to current frontline treatments. PROSPERO protocol registration number: CRD42020202377.